A new nothogenus and a new nothospecies in the subtribe Laeliinae (Orchidaceae) from Mexico - Ramos-Roldán, Andrés E.; Cuéllar-Martínez, Manuel; Lozano-Rodríguez, Miguel A.; Solano, Rodolfo (Phytotaxa, 2025)
A new nothogenus in Orchidaceae Juss. is described, resulting from the natural cross between Dinema and Nidema, for which the name × Dinedema is proposed. The putative species involved in this intergeneric cross are Dinema polybulbon and Nidema boothii. The resulting nothospecies from this cross is described here as × Dinedema mariae, which originated in the central region of Veracruz, Mexico, where its parental species coexist sympatrically. A description, plate, habitat information, and phenology of the new nothospecies is provided, along with a morphological comparison with its parental species. A spatial distribution model for D. polybulbon and N. boothii is presented, showing their overlap in the area where the hybrid originated.